2002
DOI: 10.1183/09031936.02.00211902
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with chronic alveolar hypoventilation

Abstract: Measurements of health-related quality of life (HRQL) have not been reported in patients with chronic alveolar hypoventilation (CAH) before starting home mechanical ventilation. The purpose of this study was to investigate quality of life in a population of such patients.Forty-four consecutive patients with CAH due to previous polio, scoliosis, healed pulmonary tuberculosis or neuromuscular disease answered a battery of condition specific and generic (Sickness Impact Profile, Hospital Anxiety and Depression sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 29 publications
2
45
0
2
Order By: Relevance
“…Age, the underlying disease and the severity of hypoventilation relate to these decrements in HRQoL [6]. In patients with COPD and CRF, there is an increased impact of the disease on the patients’ well-being, with the reduction in daily activities being one of the main consequences [7].…”
Section: Introductionmentioning
confidence: 99%
“…Age, the underlying disease and the severity of hypoventilation relate to these decrements in HRQoL [6]. In patients with COPD and CRF, there is an increased impact of the disease on the patients’ well-being, with the reduction in daily activities being one of the main consequences [7].…”
Section: Introductionmentioning
confidence: 99%
“…The data represent a post hoc analysis of the previously mentioned prospective study [14,15]. We observed that patients who were evaluated by 8 years had a base-line HRQL profile that was significantly less compromised compared with patients who had discontinued NPPV prematurely or died prior to the follow-up [14], indicating that baseline HRQL assessment may have a prognostic value.…”
Section: Introductionmentioning
confidence: 92%
“…Clinical characteristics of the study patients have been presented in detail elsewhere [15] and are summarised in Table 1. The median age of all patients was 66 years, and the major diagnoses were previous polio (n = 12), tb sequel (n = 17) and scoliosis (n = 11).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Others tend to underestimate the quality of life of ventilator users [91]. Recently an adult population suffering from chronic alveolar hypoventilation due to neuromuscular or restrictive disorders, and who did not receive ventilatory assistance, was reported to have severely impaired health-related quality of life [92]. The effects of respiratory assistance on growth, development, cognition, social interaction and other activities in the child still awaits further research.…”
Section: Family Issuesmentioning
confidence: 99%